Global Attractor of Hindmarsh-Rose Equations in Neurodynamics (Journal of Nonlinear Modeling and Analysis, 2024)
Global dynamics for a new mathematical model in neurodynamics of the diffusive Hindmarsh-Rose equations on a bounded domain is investigated in this paper. The existence of a global attractor and its regularity are proved through uniform estimates showing the dissipative properties and the asymptotically compact and smoothing characteristics.